Systems engineering : - Hitchins, Derek K (John Wiley, 2007)
This book conceives, presents and exemplifies a contemporary, general systems methodology that is straightforward and accessible, providing guidance in practical application, as well as explaining concept and theory. The book is presented both as a text for students, with topic assignments, and as a reference for practitioners, through case studies